4.1k views
3 votes
If f(x)=2x-1 and g(x)=x^2-3x-2 find (f+g)(x)

User Pimaster
by
5.8k points

2 Answers

2 votes

Answer:

(f+g)(x) = x²-x-3

Explanation:

We have given functions.

f(x)=2x-1 and g(x)=x²-3x-2

We have to find the sum of two functions.

(f+g)(x) = ?

The formula to find the sum of two function:

(f+g)(x) = f(x) + g(x)

Putting given values in above formula, we have

(f+g)(x) = 2x-1+x²-3x-2

Adding like terms, we have

(f+g)(x) = x²+(-3+2)x+(-1-2)

(f+g)(x) = x²+(-1)x+(-3)

(f+g)(x) = x²-x-3 which is the answer.

User Dharam Gollapudi
by
5.1k points
1 vote

Answer:


(f+g)(x)=x^2-x-3.

Explanation:

The given functions are;


f(x)=2x-1

and


g(x)=x^2-3x-2

Recall that;


(f+g)(x)=f(x)+g(x)


\Rightarrow (f+g)(x)=2x-1+x^2-3x-2.

Regroup the like terms to get;


(f+g)(x)=x^2-3x+2x-2-1.

Simplify;


(f+g)(x)=x^2-x-3.

User Adiel Mittmann
by
5.1k points